Analysis of Students’ Critical Thinking Skills in Dynamic Fluid Concepts at MA Al-Azhar Center - Melati, Sariya; Marlina, Leni; Ismet, Ismet (Universitas Islam Negeri Ar-Raniry, 2026)
This study aims to analyze the critical thinking skills of eleventh-grade students at MA Al-Azhar Center Baturaja on dynamic fluid concepts based on the critical thinking indicators proposed by Robert H. Ennis. The research employed a descriptive quantitative approach using a saturated sampling technique, involving 30 students as the research subjects. The instrument used was a multiple-choice test consisting of 15 items covering seven critical thinking sub-indicators adapted from Ennis’ critical thinking framework, namely problem formulation, argumentation, deduction, interpretation, induction, evaluation, and decision-making and implementation. Data were collected after the completion of the learning process and analyzed descriptively by calculating the percentage of achievement for each indicator. The results indicate that students’ critical thinking skills are in the moderate category and are not evenly distributed across all indicators. The highest achievement was found in the induction indicator (58.33%), while the lowest was in problem formulation (33.33%). Other indicators, such as argumentation (51.67%), deduction (46.67%), interpretation (41.67%), evaluation (53.33%), and decision-making and implementation (52.22%), were also categorized as moderate. These findings suggest that students still experience difficulties in the initial stages of critical thinking, particularly in understanding and interpreting problems. Therefore, more comprehensive instructional strategies that emphasize the development of critical thinking skills are needed to optimally improve students’ abilities.